Barriers to help-seeking among correction officers: examining the influence of institutional culture and structure - Wills, Candence (Promoting wellness and resiliency in correctional officers, 2023)
Correction officers experience a challenging work environment that increases the risk of encountering violence, physical danger, and traumatic events such as inmate violence and potential assaults by inmates. The demanding work climate can lead to stress and mental health concerns. However, officers are reluctant to seek help for their own mental health concerns and avoid employer provided services, including peer-to-peer support units. This study seeks to explore the underlying institutional barriers to help-seeking for mental health concerns among correction officers. Content analysis is applied to qualitative data from 42 semi-structured interviews with family members and friends of correction officers who died by suicide and 395 interviews with officers working for a state department of corrections answering open-ended questions. Two overarching themes emerged and within these themes were a series of subthemes revealing institutional barriers to help-seeking for mental health concerns. Institutional culture centers around stigma related to mental health and hypermasculinity perpetuated in the work environment. Institutional structure contains institutional organization, confidentiality, and punitive responses as subthemes. Correctional settings could benefit from reducing stigma of mental health related encouraged by hypermasculinity, restructuring organizational hierarchies, enforcing confidentiality, and creating supportive environments for officers to seek help for mental health concerns.